(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Congenital Rubella Syndrome (CRS) remains a significant public health concern in countries with inadequate rubella vaccination coverage. Regardless of global development toward rubella control, limited data are available from Pakistan, specifically concerning the clinical profile and laboratory-confirmed occurrence of CRS in infants. To determine the frequency of laboratory-confirmed CRS among suspected infants and to illustrate the related clinical features at a tertiary care hospital in Karachi, Pakistan. Methods: A cross-sectional study was conducted at the Department of Pediatrics, Civil Hospital Karachi on 140 infants under 12 months of age. Suspected infants of having CRS based on clinical criteria, were enrolled using non-probability consecutive sampling. Clinical features including cataract, congenital heart disease, hepatosplenomegaly, jaundice, and microcephaly were recorded. Blood samples were collected and tested for rubella-specific IgM in infants <6 months and IgG in those aged 6–12 months. Data were analysed using SPSS version 21. Frequencies and percentages were calculated, and the Chi-square test was used to determine associations between clinical features and CRS status. Results: Out of 140 suspected cases, 54 infants (38.6%) were laboratory-confirmed as CRS positive. Microcephaly (68.5%) and jaundice (72.2%) were significantly more common among CRS-positive infants (p < 0.001). Conversely, congenital heart disease (20.4%) and cataract (14.8%) were more prevalent in CRS-negative infants, a finding contrary to expected clinical trends. Pigmentary retinopathy was observed only in CRS-negative cases (5.7%). The differences in clinical presentation suggest the need for comprehensive diagnostic protocols. Conclusion: The high occurrence of CRS in this cohort underlines the sustained burden of rubella in Pakistan. Findings emphasize the importance of integrating clinical evaluation with laboratory confirmation for precise diagnosis. Improved rubella vaccination attempts and timely management are desperately required to prevent CRS-related complications and decrease its occurrence in susceptible populations.